Physicochemical, Microbiological, and Organoleptic Characteristics of IPB D1 Braised (Ungkep) Chicken at Different Storage Temperature and Different Storage Time - D. Nafisah; Z. Wulandari; A. Apriantini; C. Sumantri (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2024)
Braised (Ungkep) chicken is one of the varieties of processed IPB D1 chicken that can be produced to increase consumer acceptance. The aim of this research was to analyze the physicochemical, microbiological and organoleptic characteristics of IPB-D1 braised chicken at refrigerator and freezertemperatures with storage times of 0, 7, and 14 days. A factorial completely randomized design was used in this study. The pH value and Total Plate Count (TPC) were significantly influenced by storage time (P<0.05). The storage temperature factor and the interaction between temperature and storage time did not have a significant effect on all variables. The TPC value up to the 14th day was still below the maximum limit, therefore it was still safe to consume.